Government Credibility, Official Communication, and Destination Reputation after Crisis: A Systematic Literature Review - Dedy Iswanto; Lia Febria Lina; Ziqrurrahman Irsyad; Muhammad Fuzail (Centre of Excellence in Tourism Udayana University, 2026)
In the aftermath of a crisis, rebuilding destination reputation and restoring tourist confidence is critical, where government credibility and effective communication are vital for regaining trust. This study aims to examine the factors that influence tourist confidence and destination reputation post-crisis, focusing on the impact of public policy, crisis communication strategies, and institutional trust, and develops a conceptual model for managing destination recovery and sustainability. This study employs a systematic literature review based on the PRISMA framework, using the Scopus database, and focusing on articles published from 2020 to 2025. After applying inclusion and exclusion criteria, 22 articles were selected. A bibliometric analysis using VOSviewer was performed to map the relationships and trends in the studies included. Crisis communication, institutional trust, transparency, and government responses have proven to be pivotal in rebuilding trust and destination image. Additionally, social media, user-generated content, and influencer marketing are integral in maintaining loyalty and driving revisit intentions. The integration of public policy, strategic communication, and digital media is essential in restoring destination reputation post-crisis. Governments must leverage transparency, consistency in messaging, and social media to rebuild public trust and enhance the tourist experience. This study offers a new framework for post-crisis communication strategies, emphasizing the role of government credibility and consistent messaging in restoring tourist trust and destination reputation.